معوقات تطبيق الإدارة الإلكترونية دراسة مسحية على شركات الاتصالات في اللاذقية - ديب, صلاح محمد; منصور, ديما عدنان (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدفت هذه الدراسة إلى دراسة المعوقات والمشكلات التي تواجه شركات الاتصالات في اللاذقية في تطبيق الإدارة الالكترونية، ومحاولة التوصل إلى مجموعة من التوصيات والمقترحات التي من المتوقع أن تساعد الشركات محل الدراسة على تذليل تلك المعوقات. ولتحقيق ذلك قام الباحث بدراسة العلاقة بين وجود كل من المعوقات( الإدارية، المالية، التشريعية، التقنية، البشرية، الأمنية), وبين تطبيق الإدارة الالكترونية.وقد تمّ ذلك من خلال دراسة مسحية على شركات الاتصالات في اللاذقية (المؤسسة العامة للاتصالات، شركة سيريتل)، وكان حجم عينة البحث /60/ مفردة، وتوصلت الدراسة إلى وجود علاقة بين كل من المعوقات (الإدارية، المالية، التشريعية، التقنية، البشرية، الأمنية), وبين تطبيق الإدارة الالكترونية.This study aimed to examine the obstacles and problems that facing the telecommunications companies in Lattakia in electronic management application, and try to reach a set of recommendations and proposals that are expected to help the companies under study to overcome these obstacles. To achieve this, the researcher analyzed the relationship between the presence of all of the obstacles (administrative, financial, legislative, technical, human, and security), and the application of electronic management.This was done through a survey on telecommunications companies in Latakia (PTC, Syriatel) company,The size of research sample was /60/unit.The study found that there is a relationship between the presence of all of the obstacles (administrative, financial, legislative, technical, human, and security), and the application of electronic management in the companies under study.